Analysis of the Rehabilitation Efficacy and Nutritional Status of Patients After Endoscopic Radical Thyroidectomy by Fast Track Surgery Based on Nutritional Support - Qu, Fang; Bu, Hongxia; Yang, Liu; Liu, Hui; Xie, Chaoying (Frontiers in Surgery, 2022)
Objective :To investigate and analyze the effect of fast track surgery (FTS) based on nutritional support on the improvement of rehabilitation efficacy and nutritional status of patients after radical lumpectomy for thyroid cancer. Methods :86 patients admitted to our hospital for radical lumpectomy for thyroid cancer between April 2018 and April 2021 were selected, of which 40 patients admitted between April 2018 and April 2019 were included in the control group with conventional perioperative care. 46 patients admitted between May 2019 and April 2021 were included in the trial group with FTS care based on nutritional support. Results The patients in the trial group had shorter feeding time, hospitalization time and time out of bed than the control group (P < 0.05). The postoperative DCL-90 scores of the trial group were lower than those of the control group (P < 0.05); the GQOLI-74 scores and total scores of the trial group were higher than those of the control group at the 3-month postoperative follow-up (P < 0.05). The overall incidence of complications such as hoarseness, choking on water, hand and foot numbness, wound infection, and hypocalemia was lower in the trial group than in the control group (P < 0.05). Conclusion :The implementation of FTS care based on nutritional support for patients after endoscopic radical thyroidectomyr can effectively improve the postoperative recovery and reduce their pain level, as well as help improve their nutritional status, negative emotions and improve their quality of life, which is worth promoting.